REVIEW ON PROTEIN FOOTPRINTING AS A TOOL IN STRUCTURAL BIOLOGY - Oluwatosin Ogundairo; Oluwatoyin Ayo-Farai; Chinedu Paschal Maduka; Chiamaka Chinaemelum Okongwu; Abdulraheem Olaide Babarinde; Olamide Sodamade (Science Heritage Journal)
Structural characterization of proteins is fundamental for understanding their functions and interactions within cellular environments. Protein footprinting has emerged as a powerful and versatile technique in structural biology, providing valuable insights into protein structure, dynamics, and conformational changes. This study comprehensively explores the principles, methodologies, and applications of protein footprinting as an indispensable tool in structural biology. Protein footprinting encompasses a range of innovative techniques, including hydroxyl radical footprinting, mass spectrometry-based footprinting, and chemical footprinting, each offering unique advantages for probing different aspects of protein structure. The study elucidates the underlying principles of these methods, discussing the mechanisms by which protein-footprinting agents interact with amino acid residues and elucidate structural details. The application of protein footprinting in studying protein-protein interactions, ligand binding, and conformational changes is highlighted through a detailed examination of key studies and experimental approaches. The review emphasizes the versatility of protein footprinting in investigating diverse protein systems, from small globular proteins to large multi-subunit complexes. Furthermore, the integration of protein footprinting with other structural biology techniques, such as X-ray crystallography, NMR spectroscopy, and cryo-electron microscopy, is explored to showcase the complementary nature of these approaches in achieving a comprehensive understanding of protein structure and function. The study addresses recent advancements and technological innovations in protein footprinting methodologies, including advancements in mass spectrometry instrumentation and data analysis strategies. Additionally, it discusses challenges associated with the technique, such as data interpretation and accessibility, and proposes future directions for overcoming these hurdles. Protein footprinting stands as a valuable tool in the structural biologist’s arsenal, providing unique perspectives on protein structure and dynamics. As the field continues to evolve, with ongoing refinements in methodologies and expanded applications, protein footprinting is poised to play a pivotal role in unraveling the complexities of biological macromolecules. This study serves as a comprehensive resource for researchers and practitioners seeking an in-depth understanding of protein footprinting and its contributions to advancing structural biology.